Accident Analysis Due To The Condition Of Transportation Infrastructure In Surabaya: (Case Study on the Road Dr. Ir. H. Soekarno Surabaya) - A Wahab Sholeh A.S; Atik Wahyuni (Journal of World Conference (JWC), 2020)
The city of Surabaya is one of the major cities in Indonesia and is the capital of East Java Province, with a total population of 2,765,487 based on the Surabaya City Statistics Center 2018. With increasing population, ownership of private vehicles and activities on the highway will also increase. more dense and certainly can cause traffic accidents. The purpose of this research was to find out the characteristics of road users and the effect of the level of accidents on the road Dr. Ir. H. Soekarno Surabaya. The factors reviewed from this study are the characteristics of road users based on Age, Profession, Driver Factors, Vehicle Factors and Road Infrastructure Factors. To find out whether Dr. Ir. H. Soekarno is a road with a Black Spot area, so the Accident Rate method is used for this study to determine the accident rate based on the Black Spot area. From the results of accident analysis based on the characteristics of the road user Dr. Ir. H. Soekarno, the highest factor as the main cause of traffic accidents is caused by Drivers with speeding conditions and vulnerable drivers aged 16-30 years. And based on the accident rate method get the highest yield of 12.74 accidents / km. Year and included in the black spot area with an accident rate >1.0. The number of traffic violations and traffic accident victims on the road Dr. Ir. H. Soekarno during 2018 there were 61 traffic accidents which resulted in 7 casualties died, 7 accident victims suffered serious injuries and 73 accident victims suffered minor injuries.